Ovarian Torsion after Hysterectomy: Case Report and Concise Review of the Reported Cases - Demetrio Larraín; Andrés Casanova; Iván Rojas (Case Reports in Obstetrics and Gynecology)
Ovarian torsion after hysterectomy is a rare event. The diagnosis of ovarian torsion is challenging because symptoms are nonspecific. We present a case of ovarian torsion 2 years after laparoscopic hysterectomy (LH). Furthermore, we performed a literature review about ovarian torsion after hysterectomy. This case shows that, in cases of acute onset pelvic pain in patients with history of hysterectomy, the adnexal torsion must be kept in mind in the differential diagnosis, especially in those women who had undergone LH.